Analysis of Key Genes and miRNA-mRNA Networks Associated with Glucocorticoids Treatment in Chronic Obstructive Pulmonary Disease - Wu JJ; Zhang PA; Chen MZ; Zhang Y; Du WS; Li XN; Ji GC; Jiang LD; Jiao Y; Li X (International Journal of COPD, 2024)
Jian-Jun Wu,1 Ping-An Zhang,1 Ming-Zhe Chen,2 Yi Zhang,1 Wei-Sha Du,1 Xiao-Ning Li,1 Guo-Chao Ji,1 Liang-Duo Jiang,3 Yang Jiao,4,* Xin Li5,* 1Respiratory Department, The Third Affiliated Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Infectious Disease Department, Henan Provincial Hospital of Traditional Chinese Medicine, Zhengzhou, Henan, People’s Republic of China; 3Respiratory Department, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 4Respiratory Department, Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 5Glaucoma Department, Eye Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Li, Glaucoma Department, Eye Hospital, China academy of Chinese Medical Sciences, Beijing, People’s Republic of China, Email doudou8295@163.comBackground: Some patients with chronic obstructive pulmonary disease (COPD) benefit from glucocorticoid (GC) treatment, but its mechanism is unclear.Objective: With the help of the Gene Expression Omnibus (GEO) database, the key genes and miRNA-mRNA related to the treatment of COPD by GCs were discussed, and the potential mechanism was explained.Methods: The miRNA microarray dataset (GSE76774) and mRNA microarray dataset (GSE36221) were downloaded, and differential expression analysis were performed. Gene Ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed on the differentially expressed genes (DEGs). The protein interaction network of the DEGs in the regulatory network was constructed with the STRING database, and the key genes were screened through Cytoscape. Potential downstream target genes regulated by differentially expressed miRNAs (DEMs) were predicted by the miRWalk3.0 database, and miRNA-mRNA regulatory networks were constructed. Finally, some research results were validated.Results: ① Four DEMs and 83 DEGs were screened; ② GO and KEGG enrichment analysis mainly focused on the PI3K/Akt signalling pathway, ECM receptor interaction, etc.; ③ CD2, SLAMF7, etc. may be the key targets of GC in the treatment of COPD; ④ 18 intersection genes were predicted by the mirwalk 3.0 database, and 9 pairs of miRNA-mRNA regulatory networks were identified; ⑤ The expression of miR-320d-2 and TFCP2L1 were upregulated by dexamethasone in the COPD cell model, while the expression of miR-181a-2-3p and SLAMF7 were downregulated.Conclusion: In COPD, GC may mediate the expression of the PI3K/Akt signalling pathway through miR-181a-2-3p, miR-320d-2, miR-650, and miR-155-5p, targeting its downstream signal factors. The research results provide new ideas for RNA therapy strategies of COPD, and also lay a foundation for further research.Keywords: COPD, GC, GEO database, miRNA-mRNA, DEMs, DEGs